Seal and sealing in the Kura-Araxes culture: New findings from northwestern Iran - Abedi, Akbar (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Administrative evidences such as seal, seal making and seal impression are not common in the Kura-Araxes culture and considered as a rare finding why the total seals reported from Kura-Araxes sites in northwestern Iran, the southern Caucasus and Eastern Anatolia does not exceed one dozen. First and second seasons of excavation in Kul Tepe Gargar brought to light a stamp and a cylinder seals that are considered as the first evidence of seal and seal making in the Kura –Araxes culture in northwestern Iran. Between these seals, cylinder one contains special and unique design that known as the double-spiral or spiral horns in the shape of a ram’s horn or owl or human eye as a symbol of Kura-Araxes culture. As this design and symbol revealed in Kura-Araxes culture on different objects such as pottery, metal objects and other jewelry and ornaments, its appearance on the seal design proof of many changes in the economic and social organization of the Kura-Araxes culture. This seal dates back to 2900-2850 cal. BC. Since these seals are among the first evidences of administrative, economic and social ownership and property in this region of Iran, their introduction and identification can play an effective role in reconstructing the social behavior and could be considering as possible indicators of administrative control in the Kura-Araxes societies.